La generación e implementación de la estrategia en una empresa y su influencia en las políticas de calidad en la industria ecuatoriana: un estudio de caso - Najera, Santiago (2017)
The generation and implementation of the strategy in a company and their influence on quality policies are a key strategic issue to be studied. And the method of study of the case is a valid alternative to carry out an exhaustive qualitative investigation that allows to obtain a significant understanding of the specific case